Innovative grassland management systems for environmental and livelihood benefits - Kemp, David R.; Guodong, Han; Xiangyang, Hou; Michalk, David L.; Fujiang, Hou; Jianping, Wu; Yingjun, Zhang (National Academy of Sciences, 2013)
Grasslands occupy 40% of the world’s land surface (excluding Antarctica and Greenland) and support diverse groups, from traditional extensive nomadic to intense livestock-production systems. Population pressures mean that many of these grasslands are in a degraded state, particularly in less-productive areas of developing countries, affecting not only productivity but also vital environmental services such as hydrology, biodiversity, and carbon cycles; livestock condition is often poor and household incomes are at or below poverty levels. The challenge is to optimize management practices that result in “win-win” outcomes for grasslands, the environment, and households. A case study is discussed from northwestern China, where it has been possible to reduce animal numbers considerably by using an energy-balance/market-based approach while improving household incomes, providing conditions within which grassland recovery is possible. This bottom-up approach was supported by informing and working with the six layers of government in China to build appropriate policies. Further policy implications are considered. Additional gains in grassland rehabilitation could be fostered through targeted environmental payment schemes. Other aspects of the livestock production system that can be modified are discussed. This work built a strategy that has implications for many other grassland areas around the world where common problems apply.